Mitochondrial Complex 1, Sigma 1, and Synaptic Vesicle 2A in Early Drug‐Naive Parkinson's Disease. Issue 8 (29th April 2020) - Wilson, Heather; Pagano, Gennaro; de Natale, Edoardo Rosario; Mansur, Ayla; Caminiti, Silvia Paola; Polychronis, Sotirios; Middleton, Lefkos T.; Price, Geraint; Schmidt, Karl F.; Gunn, Roger N.; Rabiner, Eugenii A.; Politis, Marios
Abstract: Background: Dysfunction of mitochondrial energy generation may contribute to neurodegeneration, leading to synaptic loss in Parkinson's disease (PD). The objective of this study was to find cross‐sectional and longitudinal changes in PET markers of synaptic vesicle protein 2A, sigma 1 receptor, and mitochondrial complex 1 in drug‐naive PD patients. Methods: Twelve early drug‐naive PD patients and 16 healthy controls underwent a 3‐Tesla MRI and PET imaging to quantify volume of distribution of [ 11 C]UCB‐J, [ 11 C]SA‐4503, and [ 18 F]BCPP‐EF for synaptic vesicle protein 2A, sigma 1 receptor, and mitochondrial complex 1, respectively. Nine PD patients completed approximately 1‐year follow‐up assessments. Results: Reduced [ 11 C]UCB‐J volume of distribution in the caudate, putamen, thalamus, brain stem, and dorsal raphe and across cortical regions was observed in drug‐naive PD patients compared with healthy controls. [ 11 C]UCB‐J volume of distribution was reduced in the locus coeruleus and substantia nigra but did not reach statistical significance. No significant differences were found in [ 11 C]SA‐4503 and [ 18 F]BCPP‐EF volume of distribution in PD compared with healthy controls. Lower brain stem [ 11 C]UCB‐J volume of distribution correlated with Movement Disorder Society Unified Parkinson's Disease Rating Scale part III and total scores. No significant longitudinal changes were identified in PD patients at follow‐up compared with baseline. Conclusions: Our findings represent the first in vivo evidence of mitochondrial, endoplasmic reticulum, and synaptic dysfunction in drug‐naive PD patients. Synaptic dysfunction likely occurs early in disease pathophysiology and has relevance to symptomatology. Mitochondrial complex 1 and sigma 1 receptor pathology warrants further investigations in PD. Studies in larger cohorts with longer follow‐up will determine the validity of these PET markers to track disease progression. © 2020 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.